Family income effects on mathematics achievement: their relative magnitude and causal pathways. (2nd November 2019) - Marks, Gary N.; Pokropek, Artur
ABSTRACT: This study examines the influence of family income on student achievement in mathematics utilising data from the parents' questionnaire for nine countries participating in the OECD's 2012 PISA study. It finds non-trivial effects for family income that were consistently larger than, or comparable to, the effects of more commonly used measures of socio-economic background: parents' education and occupational status. Its effects ranged from weak (Hong Kong and Macau) to moderate (Belgium, Chile and Portugal) and were often stronger than the effects of parents' education and occupational status. There was no evidence that the effects of family income were mediated through cultural resources, wealth (indexed by household possessions) or educational resources in any country. This suggests that the effects of family income reflect largely unmeasured aspects of families rather than resources in the home. In Belgium and Portugal, much of the effect of family income could be attributed to prior knowledge and skills in mathematics.